2017
DOI: 10.1042/bsr20171257
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin enhances radiation response in radioresistant A549 cells by reducing protein phosphatase 2A

Abstract: Protein phosphatase 2A (PP2A) is a ubiquitous multifunctional enzyme usually known as a tumor suppressor. Recent studies have reported that although inhibition of PP2A leads to acceleration of cell growth, it also induces damaged cells to pass through the cell cycle and renders them sensitive to radiotherapy. Here, we investigated the radiosensitizing effects of digoxin as a PP2A inhibitor in two non-small-cell lung cancer (NSCLC) cell types (H460 and A549) with differential sensitivity to radiation. Digoxin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Recently, digoxin was reported to act as radio-sensitizer, by inhibiting DSB repair and therefore potentiating DNA damage caused by IR treatment. The report indicated that digoxin could elevate the expression of gH2AX, promote the formation of gH2AX foci, and reduce the expression of RAD51 (Lu et al, 2014;Surovtseva et al, 2016;Lee et al, 2017), consistent with our finding in this study. Besides, we found that digoxin reduced the expression of XRCC1 and increased the expression of RPA.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, digoxin was reported to act as radio-sensitizer, by inhibiting DSB repair and therefore potentiating DNA damage caused by IR treatment. The report indicated that digoxin could elevate the expression of gH2AX, promote the formation of gH2AX foci, and reduce the expression of RAD51 (Lu et al, 2014;Surovtseva et al, 2016;Lee et al, 2017), consistent with our finding in this study. Besides, we found that digoxin reduced the expression of XRCC1 and increased the expression of RPA.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, studies have shown that HIF-1α was involved in the process of chemoresistance, and inhibition of HIF-1α will increase the sensitivity of cancer cell to chemotherapeutic drugs [45], [46], [47]. In addition, Lee et al found that digoxin had a novel function as a phosphatase 2A (PP2A) inhibitor, and enhanced the radiosensitivity of radioresistant NSCLC cells through inhibiting PP2A [48]. These previous studies indicated that digoxin-mediated reversing of gemcitabine resistance in gemcitabine-resistant pancreatic cancer cells might be associated with inhibition of HIF-1α and PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al showed that digoxin not only enhanced DNA damage following IR treatments, but also reduced the levels of DNA repair proteins [ 60 ]. The study reported reduced expression and levels of Rad51, ERCC1, BRCA2, Ku70, Ku86, and DNA-PKcs in A549 cells but not H460 cells.…”
Section: Mechanism Of Cgs Via Dna Damage Signalingmentioning
confidence: 99%